Anarchist entrepreneurs? - Coignet, Adeline (2024)
From anarchist bakeries to anarchist bookstores, restaurants, bike repair shops, or art stores, anarchists do engage in entrepreneurship in some forms. As shown in the literature, organising is crucial for anarchists; yet, to date, few scholars have looked into potential crossovers between anarchism and entrepreneurship. Anarchists being anti-capitalist by nature, and entrepreneurs aligning within capitalist structures, leads us to question how these seemingly incompatible concepts do co-exist for individual anarchist entrepreneurs.